2015
DOI: 10.5539/mas.v9n5p295
|View full text |Cite
|
Sign up to set email alerts
|

Image Segmentation Method Selection for Vehicle Detection Using Unmanned Aerial Vehicle

Abstract: This article discusses the possibility of applying the methods of allocating super pixels in the task for detecting moving and stationary vehicles in images obtained from the unmanned aerial vehicle (UAV) which flying over roads and parking lots. The paper will also consider the specificity of images obtained when shooting with the UAV, the specificity of the image processing, and formed the requirements for segmentation algorithm applicable to the task. Author of the article has developed the application requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…object Localization with selective search There are two main traditional approaches for object localization in images: segmentation and exhaustive search. Segmentation tries to break a single partitioning of an image into its unique objects before any recognition (16). This is sometimes extremely difficult if there are disparate hierarchies of information in the image.…”
Section: Proposed Approachmentioning
confidence: 99%
“…object Localization with selective search There are two main traditional approaches for object localization in images: segmentation and exhaustive search. Segmentation tries to break a single partitioning of an image into its unique objects before any recognition (16). This is sometimes extremely difficult if there are disparate hierarchies of information in the image.…”
Section: Proposed Approachmentioning
confidence: 99%
“…High average image processing time makes MBC and Quick shift algorithms unsuitable for on-board use. SLIC algorithm is unsuitable due to a poor quality of segmentation (for a detailed comparison of these three algorithms, see Abramov et al, 2015). Comparison of FHS, SEEDS and SEEDS Revised algorithms has been conducted on operational images without regard to the ROI mask as per the following characteristics (Table 1) The (a)-(c) characteristics affect the performance of the entire vehicle detection system.…”
Section: Unit Of Visual Automatic Roi Determinationmentioning
confidence: 99%
“…In this study a cascading approach to the vehicle recognition has been defined. The works (Kim and Chervonenkis, 2015;Abramov et al, 2015) have suggested using the image segmentation into superpixels followed by their association in regions, this approach is also used in proposed algorithm herein. These works were inspired by (Choi and Yang, 2009) paper which applies mean shift segmentation in the Luv color space in order to extract blobs (superpixels) of the image.…”
Section: Introductionmentioning
confidence: 99%